Parâmetros genéticos em progênies de polinização aberta de Enterolobium contortisiliquum (Vell.) Morong em Luiz Antonio, SP, Brasil - Sant'ana, Vanessa Zaffani [UNESP]; Freitas, Miguel Luiz Menezes; Moraes, Mario Luiz Teixeira De [UNESP]; Zanata, Marcelo; Zanatto, Antonio Carlos Scatena; Moraes, Marcela Aparecida De [UNESP]; Sebbenn, Alexandre Magno (Instituto de Botânica, 2013)
The aim of this study was to estimate the genetic parameters on a progeny test of Enterolobium contortisiliquum, located at the Fazenda Experimental de Luíz Antônio (IF-SP), São Paulo State, Brazil, for genetic selection and seed production. The coefficients of genetic variation and heritability, as well as the genetic and phenotypic correlations for the silvicultural traits diameter at breast height (DBH) and total height of plants at the age of 19, 20, and 21 years and bifurcation (BIF) and stem straightness (RET), at the age of 19 years were estimated. The F test of analysis of variance detected significant variation among the progeny for the traits DBH, height in the three tested ages, and straightness of the trunk, which indicates that the tested population can be improved by selection among progenies. The estimation of heritability at the level of progeny (h²m, minimum of 0.50) for all traits was high and at the levels of individual plants (h²i, minimum 0.18) and within progenies (h²d, minimum of 0.14) was medium, indicating that the population can be improved by selection among and within progenies. Significant high genetic and phenotypic correlations among pairwise growth traits of the same age were detected as well as among those with different ages. Therefore, the direct selection, of a trait allows indirect selection of another. The results showed the potential of this progeny test to enhance a seed orchard by selection and seed production for commercial and environmental reforestation plans.

O objetivo deste estudo foi estimar parâmetros genéticos de teste de progênies de Enterolobium contortisiliquum, implantada na Fazenda Experimental de Luís Antônio (IF-SP), SP, para fins de seleção e produção de sementes. Foram estimados os coeficientes de variação genética e herdabilidade e correlações genéticas e fenotípicas para os caracteres silviculturais, diâmetro a 1,30 m de altura do solo (DAP) e altura total de plantas, aos 19, 20 e 21 anos de idade e para bifurcação (BIF) e retidão do tronco (RET) fuste, aos 19 anos de idade. O teste F das análises de variância detectou variações significativas entre as progênies para os caracteres DAP, altura nas três idades avaliadas e retidão do tronco, o que indica que a média populacional do teste pode ser melhorada pela seleção entre progênies. A estimativa do coeficiente de herdabilidade em nível de progênies (h²m, mínimo de 0,50) para os caracteres foi alta, e em nível de plantas individuais (h²i, mínimo de 0,18) e dentro de progênies (h²i, mínimo de 0,14) foi mediana, indicando que a população pode ser melhorada pela seleção entre e dentro de progênies. Foram também detectadas altas e significativas correlações genéticas e fenotípicas entre os caracteres de crescimento com a mesma idade, e entre aqueles com diferentes idades, portanto a seleção direta em um caráter permite a seleção indireta em outro. Os resultados mostraram o potencial de transformar este teste de progênies em um pomar de sementes para a produção de sementes para reflorestamentos comerciais e ambientais.
Genetic parameters in open-pollinated progenies of Enterolobium contortisiliquum (Vell.) Morong in Luiz Antonio, São Paulo State, Brazil
Keywords: correlações genética e fenotípica; herdabilidade; reflorestamento; timburí; variabilidade genética; genetic and phenotypic correlations; genetic variability; heritability; reforestation; timburí